2010
DOI: 10.5194/acp-10-4273-2010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation of iron in dust and biomass burning aerosols during AMMA-SOP0/DABEX: implication for iron solubility

Abstract: Abstract. The chemical composition and the soluble fraction were determined in aerosol samples collected during flights of AMMA-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 45 publications
12
101
1
Order By: Relevance
“…Clearly, field measurements of the iron fraction in the fine particles are needed to improve the estimate of iron deposition from the intense forest fires to the ocean. Moreover, the iron solubility observed for minerals in biomass burning aerosols varies by more than an order of magnitude from 0.5 % to 17.7 % (Guieu et al, 2005;Bowie et al, 2009;Paris et al, 2010). Since soluble iron has a residence time of months to years in the surface mixed layer, there may be long-term biological effects triggered by the initial rapid dissolution of the aerosol iron (Boyd and Ellwood, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, field measurements of the iron fraction in the fine particles are needed to improve the estimate of iron deposition from the intense forest fires to the ocean. Moreover, the iron solubility observed for minerals in biomass burning aerosols varies by more than an order of magnitude from 0.5 % to 17.7 % (Guieu et al, 2005;Bowie et al, 2009;Paris et al, 2010). Since soluble iron has a residence time of months to years in the surface mixed layer, there may be long-term biological effects triggered by the initial rapid dissolution of the aerosol iron (Boyd and Ellwood, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since iron from combustion sources is suggested to be more soluble than iron from dust (Chuang et al, 2005;Sedwick et al, 2007;Sholkovitz et al, 2009), biomass burning may have a pronounced effect on regional ocean fertilization (Guieu et al, 2005;Bowie et al, 2009;Paris et al, 2010). However, Guieu et al (2005) have concluded that pyrogenic inputs have little impact on the global iron budget since they represent at most 10 % of desert dust inputs.…”
Section: A Ito: Mega Fire Emissions In Siberiamentioning
confidence: 99%
“…They are assumed to be externally mixed with other aerosols in all of the size bins. We note that, however, internal mixing between dust and biomass burning particles may enhance the combustioniron solubility (Paris et al, 2010), but the process is still not well known.…”
Section: Iron Emissionmentioning
confidence: 99%
“…On a global scale, the large variability in the observed fractional iron solubility results, in part, from a mixture of different aerosol sources. Estimates of fractional iron solubility from fire combustion (1-60 %) are thought to be greater than those originating from mineral dust (1-2 %; Chuang et al, 2005;Guieu et al, 2005;Sedwick et al, 2007) and may vary in relation to biomass and fire characteristics as well as that of the underlying terrain (Paris et al, 2010;Ito, 2011). Iron associated with BB may provide information with respect to BB inputs of iron to the ocean (Giglio et al, 2013;e.g.…”
Section: Biomass Burning Aerosol Chemistrymentioning
confidence: 99%